(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hypovitaminosis D is a silent but very devastating health issue throughout the world. Socio-demographic factors have some role on the issue. Objectives: To determine the sociodemographic determinants of hypovitaminosis D among the clients attending specialized hospitals. Materials and Methods: This cross-sectional study was conducted among 264 respondents attended the Armed Forces Institute of Pathology, Dhaka Cantonment for estimation of 25(OH) D within the period of July 2017 to June 2018. Results: Respondentsmeanage was 48.23±14.05 years and themajority (68.56%) were female among themhalf (49.72%) were menopausal. All the clients were educated and majority (68.18%) had crossed the level of higher secondary. The mean ± SD of monthly family income was Taka 68824.46±23.92 and majority (57.57%) were from higher socioeconomic group. A large portion (47.35%) of the respondents was housewives followed by (26.56%) government employee. The mean± SD level of 25(OH) D of total population was 50.01±29.93 nmol/L butamong the male and female it was 50.86±28.61 nmo/L and 49.60±26.19 nmol/L respectively. Menopausal women (48.03±28.11 nmol/L) had significantly(p <0.05) less vitamin D than non-menopausal women (52.32±23.96 nmol/L) butupper-income group (52.47+23.12 nmol/L) found significantly (p <0.05) higher vitamin D than lower socioeconomic group (46.32+16.78 nmol/L). The fare skinned respondents (54.46 + 28.24 nmol/L)) had significantly(p<0.01) higher level of vitamin D than dark-skinned persons (42.59 + 16.79 nmol/L). The overall hypovitaminosis D was 84.84%. Conclusion: The prevalence of hypovitaminosis D was too high and sociodemographic determinants have a significant impact on vitamin D level. Effective measures need to be taken at all level to overcome nutritional disorder. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 173-176